Blasing Springs, Riley County - Pollock, Gretel J. (Kansas State University, The Chapman Center for Rural Studies, 2016)
This is a short history of the hotel and mineral springs community that once existed on land owned by the William Blasing family, Zeandale Township, Riley County, Kansas. Although not actually a town, Blasing Springs was a thriving enterprise employing family members and local residents for many years. The hotel was destroyed by a series of tornados in the 1940s. The author used field work, newspapers articles and advertisements, interviews, maps, and biographical studies.
Gretel Joyce Pollock, “Blasing Springs, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/174.
Keywords: Artesian wells; Blasing Springs Hotel; Deep Creek; Manhattan; Civil War; Mineral water